IMPACT OF MATERNAL ANAEMIA ON NEONATAL OUTCOMES: A SINGLE-CENTRE EXPERIENCE - Dostović Hamidović, Lejla; Skokic, Fahrija; Muratovic, Selma; Terzic, Asja (Sanamed, 2025)
Background: Maternal anaemia is one of the most common complications of pregnancy and is associated with adverse outcomes such as preterm delivery, impaired fetal development, and increased risks of morbidity and mortality in the perinatal period. The high prevalence of anaemia in pregnancy and its impact on fetal development represents a significant public health issue. The aim of this study was to analyze the influence of maternal anaemia on neonatal outcomes.Patients and Methods: In a two-year prospective study conducted at the Clinic of Gynecology and Obstetrics and the Clinic of Children's Diseases of the University Clinical Center Tuzla, 177 newborns and their mothers were analyzed—127 in the experimental group (mothers with anaemia) and 50 in the control group (without anaemia). Sociodemographic and clinical data of the mothers and newborns were collected. Data were processed using conventional statistical techniques. Ethical approval was obtained from the relevant institutional review board.Results: Of the 120 (70.58%) mothers with anaemia included in the study, 106 (88.3%) were between 18 and
Keywords: neonatal outcome; anaemia; pregnancy